Tertiary lymphoid structures in ovarian cancer - Sun, Guojuan (Frontiers in Immunology, 2024)
Ovarian cancer (OC) is a significant cause of cancer-related mortality in women worldwide. Despite advances in treatment modalities, including surgery and chemotherapy, the overall prognosis for OC patients remains poor, particularly for patients with advanced or recurrent disease. Immunotherapy, particularly immune checkpoint blockade (ICB), has revolutionized cancer treatment in various malignancies but has shown limited efficacy in treating OC, which is primarily attributed to the immunologically. Tertiary lymphoid structures (TLSs), which are ectopic aggregates of immune cells, have emerged as potential mediators of antitumor immunity. This review explores the composition, formation, and induction of tumor associated TLS (TA-TLS) in OC, along with their role and therapeutic implications in disease development and treatment. By elucidating the roles TA-TLSs and their cellular compositions played in OC microenvironment, novel therapeutic targets may be identified to overcome immune suppression and enhance immunotherapy efficacy in ovarian cancer.